Socio-economic situation of disabled people in selected communes of Łodz voivodeship – presentation of study results - Kobus-Ostrowska, Dorota; Miklaszewska, Anna (Sytuacja społeczno-ekonomiczna osób z niepełnosprawnościami w wybranych gminach województwa łódzkiego – prezentacja wyników badań, 2020)
The purpose of the article is to present the socio-economic diversity of people with disabilities in selected municipalities of the Lodz region in terms of urban and rural living environments. The analysis discussed in the paper is based on the findings of the pilot surveys conducted on a sample of 119 participants of the Occupational Therapy Workshops (OTW) run between September and December 2018. To verify hypotheses, measurements of diversification were applied, including a comparison of mean values, one-way analysis of variance (ANOVA), and correlation analysis. In this article the authors use to hypothesis: H1; and assume that the respondents are in a similar socio-economic situation. H2. The authors suppose that the level of diversity of conditions is mostly affected by disability certificate period and the degree of disability. Correlation analysis shows that a lower degree of disability goes along with the respondents’ higher assessment of the labor market situation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 117-130
Keywords: people with disabilities; housing situation; quality of life; standard of living; osoby z niepełnosprawnością; sytuacja mieszkaniowa; jakość życia; standard życia